Chionanthus megistocarpus (Oleaceae), a new species from the Western Cordillera of Colombia - Fernández-Alonso, José Luis; Cogollo-Pacheco, Álvaro Alfonso (Phytotaxa, 2016)
We describe a new species of Chionanthus (Oleaceae), from the Subandean forests of the Western Cordillera of Colombia. C. megistocarpus is similar to the Ecuadorian species C. colonchensis, but presents leaves with longer petioles [(12–)15–30(–35) mm], with obtuse leaf blades, without abaxial domatia, with longer inflorescences (10–20 cm long) and the largest fruits for this genus in the Neotropics (4.5–5 cm long).